Implementing Data-Driven Decision-Making to Improve the Quality of Education in Ethiopian Higher Learning Institutions - Asfaw, Zelalem; Alemneh, Daniel; Ferede, Bekalu; Santure, Abu; Jimma, Worku (International Journal of African Higher Education, 2025)
This paper investigates the barriers and facilitators to the adoption of data-driven decision-making (DDDM) in higher education institutions (HEIs) in Ethiopia. The study employed a three-round modified Delphi method involving a panel of experts comprising of faculty members and specialists in Information and Communication Technology (ICT). A total of 57 experts participated, and 39 barriers and 20 facilitators were identified. The top three barriers included the lack of a data-driven decision-making policy, organisational culture, and a data management policy. The availability of network infrastructure was identified as the most important facilitator. The results of the study indicate that organisational barriers are important factors in the effective implementation of data-driven decision-making to improve the quality of education in Ethiopian higher education institutions. The findings emphasise the significance of policy in overcoming obstacles and promoting a culture of data-driven decision-making in Ethiopian higher education institutions. Improved policy and effective implementation of practices can address the identified barriers.